Drug use evaluation: A two‐year retrospective review of the effectiveness and tolerability of agomelatine versus mirtazapine in patients with depressive disorder - Shek Ming Leung (Brain and Behavior, 2021)
Abstract Objective To compare the effectiveness and tolerability of agomelatine with mirtazapine in patients with depressive disorder. To illustrate the prescribing pattern of agomelatine and identify factors that affect the pattern of treatment result and therapeutic outcome of it. Methods The clinical data of patients using agomelatine or mirtazapine, 93 patients in each group, were included and reviewed in this retrospective study. Background characteristics, adverse events, therapeutic outcomes (discontinued or continued), reason of discontinuation, and the presence of positive pattern of treatment result were assessed. Positive pattern of treatment result was defined as either recovery or improvement of depressive disorder after therapy. Results Patients using agomelatine were associated with higher starting dose and higher dose titrated than mirtazapine. More patients started agomelatine due to intolerability, and less due to ineffectiveness of the previous antidepressant. More patients started agomelatine before the use of at least two selective serotonin reuptake inhibitor (SSRI)/serotonin‐noradrenaline reuptake inhibitor (SNRI). Patients using agomelatine were associated with less discontinuation due to intolerability, and less experience of adverse events within 90 days of initiation or dose increase, but more discontinuation due to ineffectiveness versus mirtazapine. The use of 50 mg resulted in less discontinuation. The use of at least two SSRI(s)/SNRI(s) before and more concomitant medications are independently associated with more discontinuation due to intolerability. The use of at least two SSRI(s)/SNRI(s) before was also associated with more adverse events. Using agomelatine as an augmentation to other antidepressant(s) and at a higher dose were independently associated with the experience of positive pattern of treatment result. Conclusion Agomelatine was more tolerable than mirtazapine, but could result in more discontinuation due to ineffectiveness. The use of higher dose and as an augmentation to other antidepressant(s) could improve the desired treatment result of agomelatine.